The Influence of Management Short-Term Optimization on the Level of Mandatory Disclosure of Corporate Information before and after the Regulation of Annual Report Disclosure - Paulina Sutrisno (The Indonesian Journal of Accounting Research, 2013)
This research intends to conduct an investigation into whether the short-term optimization by management in an effort to achieve certain earnings targets (by avoiding reporting losses or a decrease in earnings), will have an influence on the level of mandatory disclosure of corporate information. This research also examines the difference in the level of disclosure by a company suspected on conducting short-term management optimization in the conditions before and after the regulation of mandatory disclosure, which stresses the extent of the corporate information disclosure. The findings of this research show that the more management conducts short-term optimization through a budget cut on discretionary expenditures, the lower the level of mandatory disclosure of corporate information in the periods both before and after the regulation of mandatory disclosure of corporate information. These findings show the new regulation on corporate information mandatory disclosure, which stresses the extent of the corporate information disclosure in an effective way, can clearly detect companies conducting short-term optimization.